A practical method to design the solar photovoltaic system applied on residential building in Indonesia - Prisma Megantoro; Pinto Anugrah; Yusrizal Afif; Lilik Jamilatul Awalin; P. Vigneshwaran (Institute of Advanced Engineering and Science, 2021)
The use of solar PV system in Indonesia has expanded to various field and area. One example is residential buildings in urban areas. This article discusses calculation methods for designing a solar power generation system that is applied to residential buildings, such as homes, offices, or colleges. Electricity generated from the solar home system (SHS) is used to support many kinds of electrical equipments, where the electrical equipments are used by building occupants in their daily life. The calculation method is considered from the potential of solar energy and the reliability of the on-site system to generate electricity. The system is designed in an off-grid topology by exchanging connections with the public electricity grid owned by PLN. Calculation results shows that this SHS has a generation capacity of 1 kWp, 24 V 300 Ah battery storage, and a 200 W inverter. This SHS can reduce electricity usage in this sector by 18.2 kWh in average every month.